Case Report: Infliximab for hydroxychloroquine-induced AGEP with IL17A and IL36RN mutations: a case report and management considerations - Jiang, Xiaoyun; Hua, Chunting; Feng, Chenxi; Cheng, Hao (Frontiers in Pharmacology, 2025)
Acute generalized exanthematous pustulosis (AGEP) is a severe cutaneous drug reaction that typically resolves rapidly following withdrawal of the offending drug and administration of systemic corticosteroids. Infliximab, a biologic agent that inhibits TNF-α, is widely used in the treatment of various inflammatory diseases. Individuals with specific genetic risk factors may be more susceptible to severe drug-induced cutaneous reactions. Here, we report the first case of successful infliximab treatment in a pregnant woman with IL17A and IL36RN mutations who developed severe AGEP after 24 days of hydroxychloroquine use and failed to respond to conventional therapy.